A Therapeutic Education Program for patients that underwent at temporary tracheotomy and total laryngectomy: leading to improved the “Diagnostic, Therapeutic and Assistance Path” - Spito, Annalisa; Cavaliere, Bruno (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the study: Therapeutic education helps patients with a chronic disease to acquire and maintain the ability to live their life while handling their illness. Patients with temporary medium-term tracheotomy or permanent tracheostomy need to acquire skills to be able to handle the stoma, tracheal tube, related issues, and other apparatuses. This was the purpose of our therapeutic education program, which was aimed to take patients and caregiver to an efficient level of self-care. Methods: In 2018, was created a CME-accredited (Continuing Medical Education) “Workplace-based Learning Project” involving all the nurses in the Otolaryngology Head and Neck Operational Unit, along different specialists on the Disease Management Team, thereby forming an “Improvement Group”. We established parallel workgroups for bibliography research on data-based like PubMed, Cinahl, Cochrane, Google scholar, in order to obtain the information to write up a shared document. Results: We wrote out an Operational Protocol which lined up nursing skills – when handling patients with medium-term tracheotomy or tracheostomy – with scientific evidence. Our standard educational plan (customizable, based on each patient’s characteristics) promote the patient’s learning with respect to self-care. Conclusions: This project has set the basis for the improvement of the quality of assistance given to the patients and therapeutic education provided them. It has encouraged the development of the skills of the nurses involved, along with their motivation, and their integration on the Disease Management Team. But, it will be necessary in the future to further evaluate the effectiveness of the program in terms of self-care.